Prehistoric life: [the definitive visual history of life on earth] - Palmer, Douglas; Brasier, Martin; Burnie, David; Crane, Peter; DK Publishing, Inc. (New York, N.Y. : DK Pub., 2009)
With an extensive catalog at its heart, "Prehistoric Life" profiles hundreds of fascinating species in incredible detail; features breathtaking, state-of-the-art images; explores the concept of geological time; and explains the classification of species and how the evidence for their evolution is preserved and can be deciphered.
Young earth. Exploring earth's past ; The origin of the earth ; The first 500 million years ; Plate tectonics ; Changing climates ; Life and evolution ; Classification ; Mass extinctions ; Types of fossils ; Information in the fossil record ; Key fossil sites ; The geological timescale -- Life on earth. Archean ; Proterozoic ; Cambrian ; Ordovician ; Silurian ; Devonian ; Carboniferous ; Permian ; Triassic ; Jurassic ; Cretaceous ; Paleogene ; Neogene ; Quaternary -- The rise of the humans. Human relatives ; Human ancestors ; Origins of modern humans ; Out of Africa ; European hunter gatherers ; Paleolithic cave art ; After the ice.
At head of title: DK.
Subtitle from cover.
Includes index.
Keywords: Fossils; Fossils -- Pictorial works; Animals, Fossil; Animals, Fossil -- Pictorial works; Plants, Fossil; Plants, Fossil -- Pictorial works; Fossil hominids; Fossil hominids -- Pictorial works; Paleobiology; Earth (Planet) -- Origin; Earth (Planet) -- Origin -- Pictorial works